Research Prospect of Anti-Jamming Strategy for the Satellite Internet - Chen HAN; Aijun LIU; Kang AN (天地一体化信息网络)
As an important infrastructure of the national information system, the satellite internet is of great signifi cance to the national security.Thus, it needs to ensure the validity and reliability of the data transmission in the hostile jamming environment.The threat of smart jamming and the limitation of classical link-layer anti-jamming methods give rise to the new demand of intelligent and networked antijamming solutions.In view of the structural characteristics of the satellite internet and the development trend of modern communication jamming technologies, this paper analyzed the basic architecture of intelligent and networked anti-jamming.Based on the closed-loop strategic of sense-learn-prediction-decision-feedback, intelligent and active anti-jamming decision was made to realized self-confi guration and self-optimization.Based on the cooperative communication between nodes, networked anti-jamming ability was improved by the means of topology control and reconstruction, adjacent resources reallocation, and traffi c load balancing.It provided certain theoretical support for the construction of anti-jamming strategy system to achieved the cross-layer optimization, multi-domain combination, and adaptive intelligence.